Integrasi Literasi Keuangan dan Digitalisasi Usaha: Strategi Pemberdayaan UMKM di Kelurahan Nginden Jangkungan - Rizky Prasetya, Adinda; Dwi Cahyani, Amelia; Rizki Ramadhani, Mohamad; Hafizh Al-Farizi, Muhammad; Salsabila Putri, Syaqna; Setyo Budiwitjaksono, Gideon (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2026)
The Smart Finance and MSME Digitalization Program in Nginden Jangkungan Village is a community service activity created based on an analysis of the needs of MSMEs and women in the KSH group. This program combines financial management education with digital technology training as a way to face the challenges of the ever-evolving economy. In the financial section, participants are taught how to record daily cash flow, conduct monthly financial evaluations, separate business and personal funds, and set a fixed salary for business owners. Meanwhile, in the digital section, participants are trained to create an online store on Shopee and register their business location on Google Maps, using a hands-on method (learning by doing). Survey results showed that most participants felt very helped, both financially and technologically. This program has proven to be beneficial, tailored to community needs, and can be implemented in other areas. The approach used follows the principles of the Technology Acceptance Model (TAM) and the TOE Framework, which emphasize the importance of ease of use and environmental readiness in supporting MSMEs entering the digital world.